HOW EFL LEARNERS UTILIZE MULTIMODAL RESOURCES TO COMPREHEND METAPHOR USING DISNEY'S FROZEN SOUNDTRACK - Keyne Annora Yan; Mobit; Maya Rahmawati (Universitas Nias Raya, 2026)
This study explored how EFL learners utilized multimodal resources to comprehend metaphorical meanings using Disney's Frozen soundtrack in an Indonesian EFL classroom. Employing a qualitative approach within the framework of Classroom Action Research (CAR), the study involved 36 Grade 8 students at a private junior high school in Karawang, West Java, Indonesia. Data were collected through non-participant classroom observations, metaphor comprehension tasks, semi-structured interviews, and documentation, and were analyzed using Braun and Clarke's (2006) thematic analysis. The findings revealed that learners utilized multimodal resources through three interconnected processes: utilizing visual resources to interpret metaphorical meanings, utilizing songs and lyrics to construct emotional meanings, and utilizing classroom interaction for collaborative meaning-making. Although some learners experienced difficulties in interpreting unfamiliar vocabulary and complex metaphorical expressions, multimodal resources combined with teacher scaffolding supported their comprehension and engagement. These findings contribute to the growing body of research on multimodal pedagogy by providing insights into how Indonesian EFL learners utilize multiple semiotic resources to comprehend metaphorical meanings in authentic language learning contexts.